EFEKTIVITAS SENYAWA AKTIF KOMBINASI KENCUR KAEMPFERIA GALANGA DAN ILALANG IMPERATA CYLINDRICA SECARA IN VITRO TERHADAP BAKTERI GRAM POSITIF DAN BAKTERI GRAM NEGATIF - melia soniman; Denny Syaputra; Andri Kurniawan (Journal of Aquatropica Asia, 2022)
The rationale for using medicinal plants or herbs makes their use seen as playing an important role in the prevention and treatment system at the present time. Utilization of medicinal plants in combination is considered more effective and has a higher antibacterial activity compared to a single extract. One of the herbal medicine products from the combination of kencur medicinal plants (Kaempferia galanga) and thatch (Imperata cylindrica) under the name Meddia Meddwa its antibacterial activity has been assessed. This study aims to analyze the effectiveness and antibacterial activity in vitro, and the best concentration from the combination of kencur and kalang in Jamu Meddia Meddwa against Gram positive bacteria ( S. aureus) and Gram negative (A. hydrophila). This study also analyzed the content of active compounds or phytochemicals contained in the combination of kencur and thatch in Meddia Meddwa Medicines. The research method used is a laboratory experimental method. This study uses a single complete randomized design (CRD) with a tukey test. The results showed that the combination of kencur and kalang in Meddia Meddwa herbal medicine had antibacterial activity in vitro. Inhibitory zone diameters for all extract concentrations tested on A. hydrophila and S. aureus significantly different results were obtained (P ≤ 0.05). Gram-positive bacteria (A. hydrophila) effectively inhibits bacterial growth compared to Gram negative bacteria (S. aureus). The content of active compounds contained in the combination of kencur and thatch in simplicia Meddia Meddwa is alkaloids, flavonoids, steroids and phenol hydroquinone. The best concentration of simplicia kencur and thatch in Meddia Meddwa herbal medicine in inhibiting bacterial growth A. hydrophila and S. aureus is 6 ppt.